Пермский филиал по исследованию политических институтов и процессов Института философии и права УрО РАН: 10 лет со дня основания - Битковская, Т.Б.; Бедерсон, В.Д. (Perm Federal Research Centre Journal, 2013)
This article provides basic information about the Perm branch of the Institute of Philosophy and Law, the Ural Branch of RAS and provides an overview of the main directions and results of scientific research of the Institute for the period of 10 years, since the time of its foundation.